Outstanding Strengthening and Toughening Behavior of 3D-Printed Fiber-Reinforced Composites Designed by Biomimetic Interfacial Heterogeneity - Yu, Siwon; Hwang, Yun Hyung; Lee, Kang Taek; Kim, Sang Ouk; Hwang, Jun Yeon; Hong, Soon Hyung (Wiley-VCH Verlag, 2022)
3D printing of fiber-reinforced composites is expected to be the forefront technology for the next-generation high-strength, high-toughness, and lightweight structural materials. The intrinsic architecture of 3D-printed composites closely represents biomimetic micro/macrofibril-like hierarchical structure composed of intermediate filament assembly among the micron-sized reinforcing fibers, and thus contributes to a novel mechanism to simultaneously improve mechanical properties and structural features. Notably, it is found that an interfacial heterogeneity between numerous inner interfaces in the hierarchical structure enables an exceptional increase in the toughness of composites. The strong interfacial adhesion between the fibers and matrix, with accompanying the inherently weak interfacial adhesion between intermediate filaments and the resultant interfacial voids, provide a close representation of the toughness behavior of natural architectures relying on the localized heterogeneity. Given the critical embedment length of fiber reinforcement, extraordinary improvement has been attained not only in the strength but also in toughness taking advantage of the synergy effect from the aforementioned nature-inspired features. Indeed, the addition of a small amount of short fiber to the brittle bio-filaments results in a noticeable increase of more than 200% in the tensile strength and modulus with further elongation increment. This article highlights the inherent structural hierarchy of 3D-printed composites and the relevant sophisticated mechanism for anomalous mechanical reinforcement.